RUMAH SINGGAH KUCING DI BANJARMASIN - Permadi, Fajar; Oktaviana, Anna (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
The population of cats is increasing every year in the world, unfortunately, the increase in cat population is also directly proportional to the number of cases of abuse that occur. It is proven that in Banjarmasin itself there are still many acts of persecution, both intentionally and unintentionally. Responding to these problems created an abandoned cat shelter. The Design of Cat Shelter Houses in Banjarmasin is a facility that aims to meet the physical and psychological needs of cats by adopting an environmentally friendly design approach. The concept approach uses Paola Sassi's sustainable architecture, as a solution to problems with land use, health, material, energy, and water strategies, so healthy building designs that benefit residents.